SIFAT FISIKOKIMIA DAN SENSORIS ES KRIM LABU KUNING DENGAN PENAMBAHAN TEPUNG TALAS SEBAGAI PENGENTAL - Abdul Rahim; Syamsudin laude; Asrawaty Asrawaty; Akbar Akbar (Universitas Tadulako, 2017)
The objective of the research was to determine the physicochemical and sensory properties of taro flour as a thickener. The treatment used was taro flour concentrations at 5, 10, 15, 20 and 25%. The study was conducted using a Completely Randomized design for observing the physicochemical properties including overrun, melting rate, β-caroten content and protein content;and a Randomized Block design for observing the sensory properties under five treatments with three replicates. The pumpkin ice cream with addition of taro flour concentration between 10-25% can be used as thickener on ice cream making. The overrun and melting rates of ice cream pumpkin tended to decrease with increasing the taro flour concentrations. Best β-caroten and protein contentsfound inthe pumpkin ice cream are under the taro flour concentrations at 10-15%. The sensory properties of pumpkin ice cream are liked by panelists. Key words: Ice cream, Pumpkin, Taro flour, Thickener.